Optical Characteristics and Chemical Composition of Dissolved Organic Matter (DOM) from Riparian Soil by Using Excitation-Emission Matrix (EEM) Fluorescence Spectroscopy and Mass Spectrometry. Issue 5 (May 2015) - Wang, Yulai; Yang, Changming; Zou, Limin; Cui, Hengzhao
Understanding the quantity and quality of soil dissolved organic matter (DOM) in riparian buffer zones is critical for explaining the biogeochemical processes of soil DOM in river ecosystems. Here, we investigated the dissolved organic carbon, fluorescent DOM (FDOM), and DOM molecules from riparian soils on Chongming Island in eastern China. Simultaneously, the soil DOM was extensively characterized in terms of the total aromaticity index (TAI) and several optical indices. The excitation (Ex)-emission (Em) matrix parallel factor analysis results showed that two humic-like components were present (Ex/Em = 283(364)/454 nm; 337/410 nm), a fulvic-like component (Ex/Em = 241/426 nm) and a microbial degradation component (Ex/Em = 295/382 nm). The humic-like and fulvic-like substances were the main components in the riparian soil FDOM, accounting for ~90% of the FDOM. Mass spectrometry provided more detailed information for the soil DOM molecules. Six chemical fractions, amino acids, carbonyl compounds, fatty acids, lipids, proteins and sugars, were identified using liquid chromatography with quadrupole time-of-flight mass spectrometry. Lipids, proteins, and carbonyl compounds were dominant in the soil DOM, accounting for .85% of the detected molecules ( m/z < 1000). Significant differences were observed between the quantities of the six soil DOM chemical fractions at the different sampling locations. Discriminant molecules verified the hypothesis that the chemical soil DOM fractions varied with the land use of the adjacent watersheds. The TAI for the soil DOM could provide more reliable information regarding the biogeochemical processes of DOM. The carbonyl compounds and lipid fractions controlled this index. Overall, the optical indices and TAI values can improve our understanding of soil DOM quality; however, the optical indices did not provide quantitative evidence regarding the sources or properties of the soil DOM. The observations from this study provided detailed information regarding the soil DOM quality and the presence of specific molecules and improved our understanding of the biogeochemical processes of DOM.